2014
DOI: 10.1097/bot.0000000000000127
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Posterior Pelvic Imaging

Abstract: Objectives The null hypothesis of the current study states that routine axial CT images are obtained at a consistent and reproducible orientation relative to the sacrum. The secondary null hypothesis states that there is no difference in the measurement of the safe zone for placement of iliosacral screws when using routine axial CT images and standardized reconstructions in defined planes perpendicular and parallel to the sacrum. Design Retrospective review. Setting University Level-1 Trauma Center Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 13 publications
(14 reference statements)
1
22
0
Order By: Relevance
“…Due to individual sacral and lumbar anatomy, the angulation for optimal visualization of pelvic anatomy in AP, inlet and outlet radiographs is variable 41–45 . This leads to a different projection of the posterior pelvic ring and individualized outlet and inlet projection angles were proposed 46,47 . However, these individualized angles are difficult to obtain in daily routine.…”
Section: Discussionmentioning
confidence: 99%
“…Due to individual sacral and lumbar anatomy, the angulation for optimal visualization of pelvic anatomy in AP, inlet and outlet radiographs is variable 41–45 . This leads to a different projection of the posterior pelvic ring and individualized outlet and inlet projection angles were proposed 46,47 . However, these individualized angles are difficult to obtain in daily routine.…”
Section: Discussionmentioning
confidence: 99%
“…1 Percutaneous posterior pelvic ring fixation is one of the most frequently used means of fixation of the posterior ring, yet it is a technically demanding procedure. 2 The sacral morphology has a wide range of normal variations 3,4 which can make the critically important intraoperative interpretation of fluoroscopy challenging 5 ; an essential first step for a safe surgery is a careful preoperative review of a patient's specific bony anatomy to determine safe bony corridors.…”
Section: Introductionmentioning
confidence: 99%
“…Reformatting the CT scan into the inlet and outlet orientation is described. 5 This is a common practice when planning for percutaneous posterior pelvic ring fixation because it has been reported that axial nonreformatted (ANR) images provide "inconsistent safe zone measurements compared with CT inlet (axial) and outlet" (coronal) reformatted images. 5 However, the most important aspect of the preoperative review may be the identification of narrow corridors that may increase the risk of screw breach.…”
Section: Introductionmentioning
confidence: 99%
“…Malpositioning of percutaneous screws remains a problem and can cause iatrogenic nerve injury or revision surgery [9,10]. Flouroscopy in the emergency department includes one plain pelvic x-ray [11]. Diagnosis with this imaging is possible but not suitable for correct diagnosis and classifications or pre-operative planning.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis with this imaging is possible but not suitable for correct diagnosis and classifications or pre-operative planning. Further x-rays as inlet-or outlet-view are possible but 3D CT scan is gold-standard for these injuries [11,12].…”
Section: Introductionmentioning
confidence: 99%